Re-union : how bold labor reforms can repair, revitalize, and reunite the United States - Madland, David (ILR Press, an imprint of Cornell University Press, 2021)
"The central argument of this book is that stronger unions operating under a new type of labor system could help address America's underlying economic and political challenges. The new system would be built around two central ideas: active policy support for unions and broad-based collective bargaining"--